Complement C7 is a novel risk gene for Alzheimer's disease in Han Chinese. Issue 2 (5th November 2018) - Zhang, Deng-Feng; Fan, Yu; Xu, Min; Wang, Guihong; Wang, Dong; Li, Jin; Kong, Li-Li; Zhou, Hejiang; Luo, Rongcan; Bi, Rui; Wu, Yong; Li, Guo-Dong; et al.
Abstract: Alzheimer's disease is the most common neurodegenerative disease, and has a high level of genetic heritability and population heterogeneity. In this study, we performed the whole-exome sequencing of Han Chinese patients with familial and/or early-onset Alzheimer's disease, followed by independent validation, imaging analysis and function characterization. We identified an exome-wide significant rare missense variant rs3792646 (p.K420Q) in the C7 gene in the discovery stage ( P = 1.09 × 10 −6, odds ratio = 7.853) and confirmed the association in different cohorts and a combined sample (1615 cases and 2832 controls, Pcombined = 2.99 × 10 −7, odds ratio = 1.930). The risk allele was associated with decreased hippocampal volume and poorer working memory performance in early adulthood, thus resulting in an earlier age of disease onset. Overexpression of the mutant p.K420Q disturbed cell viability, immune activation and β-amyloid processing. Electrophysiological analyses showed that the mutant p.K420Q impairs the inhibitory effect of wild type C7 on the excitatory synaptic transmission in pyramidal neurons. These findings suggested that C7 is a novel risk gene for Alzheimer's disease in Han Chinese.